Hydraulic Strategy of Cactus Root–Stem Junction for Effective Water Transport - Kim, Hyejeong; Kim, Kiwoong; Lee, Sang Joon (Frontiers in Plant Science, 2018)
Cactus roots function as a hydraulic safety valve by conducting available water quickly and preventing water loss under drought condition. In particular, the root–stem (R–S) junction is responsible for effective water transport by direct coupling of the water absorptive thin roots and the moisture-filled bulky stem. In this study, the morphological features of the R–S junction were observed by using X-ray micro-imaging technique. Their structural and functional characteristics were also elucidated according to a hydrodynamic viewpoint. With regard to the axial water transport through xylem, the R–S junction prevents water leakage by embolizing large-scale vessels with relatively high hydraulic conductivity. In addition, the axial theoretical hydraulic conductivity of xylem vessels from the roots to the stem drastically increases to facilitate water absorption and prevent water loss. The cortex cell layer of a cactus is thinner than that of other plant species. In the viewpoint of radial conductivity, this property can be the hydraulic strategy of the cactus R–S junction to transport water quickly from the root surface into the xylem. These results suggest that the R–S junction functions as a hydraulic safety valve that can maximize water uptake in axial and radial directions at limited rainfall. This junction can also prevent the stem from leaking water under drought condition.